Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1186/1471-2407-14-536
|View full text |Cite
|
Sign up to set email alerts
|

T3 levels in relation to prognostic factors in breast cancer: a population-based prospective cohort study

Abstract: BackgroundThe issue of a potential association between thyroid conditions/hormones and breast cancer has been studied extensively during the last decades but the results have been inconclusive and almost no studies have investigated breast cancer aggressiveness. We have previously found a positive association between prospectively measured levels of triiodothyronine (T3) and breast cancer incidence as well as breast cancer mortality. We now investigated prediagnostic T3 levels in relation to specific prognosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 30 publications
2
25
0
2
Order By: Relevance
“…In breast cancer cell lines it has been demonstrated that tri‐iodothyronine can augment the cell proliferation potential of estrogens, thus possibly increasing the malignant potential in breast cancer cells lines . This is supported by a recent trial where higher endogenous serum tri‐iodothyronine was associated with breast tumours demonstrating more aggressive characteristics and increased mortality . However, the association with breast cancer was of borderline statistical significance in the overall group and the association was not related to the number of liothyronine prescriptions, which raises doubt as to whether this association is causally related or not.…”
Section: Discussionmentioning
confidence: 95%
“…In breast cancer cell lines it has been demonstrated that tri‐iodothyronine can augment the cell proliferation potential of estrogens, thus possibly increasing the malignant potential in breast cancer cells lines . This is supported by a recent trial where higher endogenous serum tri‐iodothyronine was associated with breast tumours demonstrating more aggressive characteristics and increased mortality . However, the association with breast cancer was of borderline statistical significance in the overall group and the association was not related to the number of liothyronine prescriptions, which raises doubt as to whether this association is causally related or not.…”
Section: Discussionmentioning
confidence: 95%
“…Evidence from epidemiological studies on postmenopausal women suggests that an increased T3/E2 ratio may promote breast cancer development (14,34,35). T3 levels have also been shown to have a positive correlation with breast cancer tumor size and the risk of lymph node metastasis in populationbased studies (36).…”
Section: Discussionmentioning
confidence: 99%
“… 13 In population-based studies, T3 levels have also been found to have a positive correlation with breast cancer tumour size and the risk of lymph node metastasis. 31 …”
Section: Discussionmentioning
confidence: 99%